Comparative genomics alaysis and molecular characterization of community and hospital-associated methicillin-resistant Staphylococcus aureus - Zarizal Suhaili
Published genomics data regarding CA-MRSA and HA-MRSA isolates from Malaysia are scarce. Therefore, the aim of this study was to characterise the Malaysian CA-MRSA and HA-MRSA isolates in depth using molecular typing, as well as whole-genome sequencing. CA-S aureus isolates were obtained from the nasal swabs of undergraduate students whereas HA-S aureus isolates were archived samples obtained from hospital laboratories. Out of 168 S aureus nasal carriage isolates obtained, the occurrence of MRSA was 8.3% and IS% among undergraduate students of the agriculture biotechnology and health sciences programmes, respectively, with multidrug resistance were observed in IS% (26/168) of the isolates. Among the 146 hospital archived samples ofS aureus, 28% (41/146) were MRS A, out of which 63% (i.e. 26/41) were categorised as multidrug-resistant (MDR; resistant to three or more classes of antimicrobial compounds).